Transition Metal Chelates of N-Hydroxy-N-Phenyl-N'-p-Anisolyl Benzamidine - Swami, V.K.; Mathur, S.P. (Asian Journal of Chemistry, 2010)
The present work is a brief report on complexing behaviour of N-hydroxy-N-Phenyl-N´-p-anisolyl-benzamidine with UO2(II), Cu(II), Pb(II), Zn(II), Co(II), Cd(II) and Mn(II).